2020
DOI: 10.1080/13880209.2020.1751661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glycyrrhizin on the pharmacokinetics of nobiletin in rats and its potential mechanism

Abstract: Context: Both nobiletin (NBL) and glycyrrhizin (GL) have anti-inflammatory and antitumor properties. These agents may be co-administered in the clinic. However, the drug-drug interaction between them is not clear. Objective: The drug-drug interaction between GL and NBL was investigated, to clarify the effect of GL on the pharmacokinetics of NBL, and its main mechanism. Materials and methods: The pharmacokinetic profiles of oral administration of NBL (50 mg/kg) in Sprague-Dawley rats of two groups with six each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Therefore, we concluded that the strong inhibitory effect of HMF was associated with the number of hydroxyl and methoxyl groups in HMF. Previous pharmacokinetic studies demonstrated that HMF reached a high plasma concentration in rats (Singh et al, 2011; Wang et al, 2020). Structurally, we speculated that, similar to TCDD, both HMF and 1‐hydroxypyrene are composed of several six‐membered benzene rings that form a π–π or p –π conjugated system.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, we concluded that the strong inhibitory effect of HMF was associated with the number of hydroxyl and methoxyl groups in HMF. Previous pharmacokinetic studies demonstrated that HMF reached a high plasma concentration in rats (Singh et al, 2011; Wang et al, 2020). Structurally, we speculated that, similar to TCDD, both HMF and 1‐hydroxypyrene are composed of several six‐membered benzene rings that form a π–π or p –π conjugated system.…”
Section: Discussionmentioning
confidence: 97%
“…The inhibition or induction of CYP450 activity plays vital roles in the metabolism and pharmacokinetics of various drugs during drug-drug interactions [ 13 ]. For example, the co-administration of nobiletin and glycyrrhizin induced adverse interactions, which resulted in a decrease of in the plasma concentration of nobiletin due to the enhancement of CYP3A4 activity by glycyrrhizin [ 14 ]. Cornin is one of the most widely used herbs in cardiology and exerts the effects of decreasing blood pressure, reversing cardiac hypertrophy, and improving heart function [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also induced the drugdrug interaction between other drugs. For example, the coadministration of glycyrrhizin and nobiletin led to the enhanced metabolism of nobiletin via inducing the activity of CYP3A4 (Wang et al 2020). Therefore, it is speculated that the effect of ligustrazine on the pharmacokinetics of valsartan was a result of the enhanced activity of CYP3A4.…”
Section: Discussionmentioning
confidence: 99%